Empirical evidence on Non-Performing Loans and credit frictions: banking sector in Tunisia - Salha Ben Salem; Moez Labidi; Nadia Mansour (International Journal of Financial, Accounting, and Management, 2020)
Purpose: This paper explores the most important determinants of friction in the Tunisian credit market. The previous literature argued that friction is largely explained by the increase in Non-Performing Loans Nkusu, 2011; Abadi et al. 2014; Rulyasri et al.2017, Roland et all, 2013. Research methodology: We constructed a multivariate Vector Error Correction Model, with five macroeconomic variables (industrial production index, the money supply, money market interest rate) to examine the impact of Non-Performing Loans increase in amplifying the Tunisian credit frictions. Results: The Vector Error Correction Model (VECM) regression results show a negative and important relationship between economic growth and Non-Performing Loans (NPL) ratio, which is very robust during the political crisis of 2011. The money market interest rate and the money supply are positively related to the Non-Performing loan ratio. Limitation: This study was only focused on Tunisian banking sector as one of the pillars of the Tunisian economy. Contributions: This highlights that the nature of the monetary policy adopted by the monetary authority of Tunisia plays a significant role in the fluctuation of the Non-Performing Loans ratio. Bank capitalization is positively and statistically significant with Non-Performing Loan ratio, implying that banks with a low level of capital are more likely to have a riskier credit portfolio that causes the increase of Non-Performing Loans in their balance sheet.